Tantangan dan Transformasi: Memahami Ancaman Kehilangan Aksara Lampung dalam Era Modernisasi - Indra Abdul Majid; Samuel Halomoan Simarmata; Tri Utami Febriyani; Siti Komariah; Mirna Nur Alia Abdullah (FKIP, Universitas Palangka Raya, 2026)
This article discusses the challenges of preserving the Lampung script in an era of increasing modernization. As part of Indonesia's cultural heritage, the Lampung script faces the risk of losing its identity due to the influences of urbanization, migration, and the dominance of mass media. The younger generation tends to have minimal understanding of the Lampung script due to a lack of emphasis in formal education and lifestyle changes that focus more on technology. This study adopts a literature review method, gathering several sources to strengthen its research. Preservation efforts are carried out through introducing the Lampung script to the younger generation through formal and informal education, developing modern technology to facilitate learning, and integrating the Lampung script into local education curricula. Collaboration between the government, cultural institutions, education sector, and the community is necessary to preserve the Lampung script as an essential part of Lampung's cultural and linguistic identity. Further research is recommended to evaluate the effectiveness of proposed preservation efforts and gain a deeper understanding of the use and understanding of the Lampung script among the Lampung community.